Pendugaan Umur Simpan Serbuk Temulawak Berbasis ASLT terhadap Berbagai Jenis Kemasan dan Suhu Penyimpanan - Dhea Putri Yosintha (Fakultas Teknologi Pertanian, 2025)
Shelf life is an important factor to consider when using a product. The use of turmeric powder as a traditional health product has become popular due to its benefits in boosting immunity, acting as a natural antimicrobial, relieving digestive disorders, and reducing the risk of heart disease. This study aims to estimate the shelf life of turmeric powder using the ASLT method. The Accelerated Shelf Life Testing (ASLT) method involves accelerating degradation reactions by storing the product under conditions exceeding normal storage conditions. The parameters used are physical and chemical characteristics, with storage treatments at temperatures of 35 °C, 45 °C, and 55 °C using PP plastic stand-up pouches and aluminum foil stand-up pouches. During storage, the turmeric powder experienced an increase in moisture content and a decrease in total dissolved solids (TDS) and solubility, while color parameters showed no significant changes. Shelf life estimates indicate that higher storage temperatures result in shorter product shelf life. Aluminum foil packaging has a longer shelf life compared to PP plastic packaging at all storage temperatures. The longest shelf life was recorded at 10°C with aluminum foil packaging, which was 236 days.
Repository Januari 2026_Hasyim
Keywords: shelf life; dip pouch; temulawak; ASLT